Antiapoptotic and antioxidative effects of cerium oxide nanoparticles on the testicular tissues of streptozotocin-induced diabetic rats: An experimental study - Torab Solgi; Iraj Amiri; Sara Soleimani Asl; Massoud Saidijam; Banafsheh Mirzaei Seresht; Tayebe Artimani (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Cerium dioxide nanoparticles (CNPs) due to the antidiabetic and antioxidant activities are proposed for the treatment of oxidative stress-associated diseases. Objective: To examine the impact of CNPs on hyperglycemia-induced apoptosis and oxidative stress in the testis of diabetic rats. Materials and Methods: Twenty-four male rats were divided into four groups (n = 6/each) as diabetic rats, CNPs group, diabetic + CNPs rats, and controls. The control group was fed only mouse food and water. Rats became diabetic through receiving streptozotocin (STZ) 60 mg/kg. CNPs were given to the rats at a dose of 30 mg/kg daily for 2 wk. Malondialdehyde and total thiol group (TTG) levels were measured using spectrofluorometer. Expression of b-cell lymphoma protein 2-associated X protein (BAX) and b-cell lymphoma protein 2 (Bcl-2) were investigated using quantitative real-time polymerase chain reaction. Western blot analysis was used to examine caspase 3 protein levels. Results: The content of malondialdehyde significantly increased in the STZ-diabetic rats, while TTG levels demonstrated a remarkable decrease. Caspase-3, BAX, and BAX/Bcl-2 mRNA ratio raised significantly in the STZ-diabetic rats. On the other hand, Bcl-2 mRNA levels reduced in the testis of diabetic rats (p = 0.006). Intervention with CNPs caused a substantial increase in the TTG levels, while the malondialdehyde contents, caspase-3, BAX levels, as well as BAX/Bcl-2 mRNA ratio were considerably decreased following CNPs treatment. Administration of CNPs increased mRNA levels of Bcl-2 (p < 0.0001). Conclusion: CNPs treatment attenuates testicular apoptosis and oxidative stress induced by diabetes. This nanoparticle might be suggested for the treatment of diabetes-associated reproductive disorders.